Quantum phase transitions in the spin-1 bilinear-biquadratic Heisenberg model based on classical and quantum correlations - Ghader Najarbashi (Scientific Reports, 2025)
Abstract We investigate thermal and non-thermal quantum correlations in the one-dimensional spin-1 bilinear-biquadratic Heisenberg model. Using tools from quantum information theory–such as generalized concurrence, negativity, and various measures of quantum, classical, and total correlations in bipartite states–we demonstrate that these measures effectively identify quantum phase transitions (QPTs) at critical points. Our negativity analysis reveals nearly identical results at zero or very low temperatures. Importantly, we find that partial concurrence, defined with the reduced density matrix $$ρ _{1,2}$$ , detects more quantum critical points than total concurrence. Additionally, we argue that spin chains with an odd number of spins are more effective than those with an even number in identifying QPTs.